Avifaunal characteristics in the altitudinal gradient of a Andean cloud forest in La Paz, Bolivia - Martínez, Omar (2007)
This study analyzes the diversity and composition of the birds at three locations within the National Park and Natural Area Integrated Management of Cotapata, La Paz, Bolivia. The three locations were distributed in altitudinal gradient and three Andean rainforests (ceja de monte -Cloud forest ridges- to 3170 m, cloud forest to 2620 m and secondary cloud forest to 1850 m) of the Yungas area. We make a total effort of 3282 mist, 324 random walks hours and 216 point counts hours in the three study sites. A total of 220 species were recorded, most caught in nets (100 spp., 45%). Twenty-five families were represented in catches by mist net and 42 through censuses. Tyrannids and Thraupids were more representatives by both methods. Species cumulative curves were similar at all sites with major cumulative number of species by census data. Species richness in the elfin forest, cloud forest and secondary forest based on netting data and count data was 44, 40, 44 species and 69, 57, 86 species, respectively. A total of 16 restricted range species were registered (e.g. Odontophorus balliviani, Andigena cucullata). Diversity for cloud forest ridges was H´= 1,41; for cloud forest (H´= 0,98) and secondary cloud forest (H´= 0,96). Beta diversity was 0,74 based on netting data and 0,79 based on count data from three elevations.